Production process for preparing polyaspartic acid based on solid superacid

The use of solid superacid SO42-/ZrO2-Al2O3 as a catalyst in the production of poly-L-aspartic acid addresses the issues of water consumption and environmental pollution in existing methods, achieving higher efficiency and catalyst recovery.

CN119638994AActive Publication Date: 2025-03-18BEIJING YANZHISHAN TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510177035.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-18
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

The existing methods for producing poly-L-aspartic acid (PLA) consume large amounts of acid as catalysts, leading to significant water usage and environmental pollution, with limited catalyst recovery and high water consumption.

Method used

A production process using solid superacid SO42-/ZrO2-Al2O3 as a catalyst in a vacuum high-temperature reaction to synthesize PLA, followed by filtration and acid regeneration, allowing for reduced water usage and catalyst recycling.

Benefits of technology

This process enhances catalyst efficiency, reduces water consumption, and simplifies the production line by avoiding acidic waste treatment, enabling the reuse and regeneration of the catalyst, thus minimizing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638994A_ABST
    Figure CN119638994A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of high-molecular polymers, and discloses a production process for preparing polyaspartic acid based on solid superacid, which comprises the following steps: by taking aspartic acid as a raw material and solid superacid SO4 < 2-> / ZrO2-Al2O3 with the particle size of more than 80 meshes as a catalyst, reacting under a vacuum high-temperature condition to obtain a polymerization product, crushing the polymerization product, screening particles with the particle size of less than 100 meshes to obtain polysuccinimide, and hydrolyzing the polysuccinimide in a sodium hydroxide or potassium hydroxide aqueous solution to obtain a sodium polyaspartate or potassium polyaspartate aqueous solution; and carrying out filtration or electrodialysis treatment on the sodium polyaspartate or potassium polyaspartate aqueous solution, sterilizing, and drying to obtain the polyaspartic acid. According to the method, solid superacid SO4 < 2-> / ZrO2-Al2O3 is used as the catalyst, so that the water resource consumption is reduced, the process route is simplified, the treatment procedure of washing acidic wastewater is avoided, and the catalytic efficiency is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer preparation, specifically relating to a production process for preparing polyaspartic acid based on solid superacid. Background Art

[0002] Polyaspartic acid is a homopolymer amino acid with aspartic acid as the monomer. Each monomer contains a free carboxyl group and a peptide bond. It is a multifunctional biopolymer material with strong moisturizing, chelating, dispersing and adsorption properties. It is widely used in water treatment agents, fertilizer enhancers, metal cutting fluids, daily chemicals, detergents, dispersants, chelating agents and water-retaining agents.

[0003] The main synthesis method for polyaspartic acid currently involves using aspartic acid as a raw material and directly undergoing high-temperature dehydration and condensation polymerization in a solid phase under the catalysis of phosphoric acid and sulfuric acid to obtain polysuccinimide. The polysuccinimide is then pulverized, washed with water to remove acid, and hydrolyzed in an aqueous sodium hydroxide solution to obtain an aqueous solution of sodium polyaspartate. This polymerization process, employing solid-phase polymerization without the use of organic solvents, reduces production costs and effectively controls environmental pollution. However, it still requires a large amount of acid as a catalyst; neither phosphoric acid nor sulfuric acid is easily recycled, and a large amount of water is needed for rinsing, leading to severe water resource consumption. Summary of the Invention

[0004] (1) Purpose of the invention The purpose of this invention is to provide a production process for preparing polyaspartic acid based on a solid superacid. This method uses SO4, a solid superacid with a suitable particle size. 2- / ZrO2-Al2O3, as a catalyst in the polymerization process, avoids the treatment of acidic wastewater from washing, saves water resources, simplifies the process route, and has higher catalytic efficiency.

[0005] (2) Technical solution To address the aforementioned problems, a first aspect of the present invention provides a production process for preparing polyaspartic acid based on a solid superacid, wherein the solid superacid used is SO4. 2- / ZrO2-Al2O3, including the following steps: S1, made from aspartic acid, using solid superacid SO4 with a particle size of 80 mesh or larger. 2- / ZrO2-Al2O3 was used as a catalyst to react under vacuum and high temperature conditions to obtain polymerization products, including polysuccinimide; S2, the polymerization product is crushed and sieved to obtain polysuccinimide with a particle size of less than 100 mesh, and then hydrolyzed in an aqueous solution of sodium hydroxide or potassium hydroxide to obtain an aqueous solution of sodium polyaspartate or potassium polyaspartate. S3 involves filtering or electrodialysis an aqueous solution of sodium polyaspartate or potassium polyaspartate until the pH of the solution drops to 3.8-4.0, followed by sterilization and drying to obtain polyaspartic acid.

[0006] Furthermore, in step S1, the aspartic acid and the solid superacid SO4 2- The mass ratio of ZrO2 to Al2O3 is 1:0.01~0.1.

[0007] Furthermore, in step S2, the molar ratio of sodium hydroxide or potassium hydroxide to polysuccinimide repeating units is 1.2 to 0.9:1.

[0008] Furthermore, the production process also includes: S4, acid titration of particles larger than 100 mesh separated in step S2, including: If the solid superacid SO4 is sieved out 2- Since ZrO2-Al2O3 particles can make the indicator develop color, they are used as the solid superacid SO4 in step S1. 2- / ZrO2-Al2O3 catalyst can be used directly; If the solid superacid SO4 is sieved out 2- If ZrO2-Al2O3 particles cannot produce color in the indicator, they are regenerated; particles with a diameter greater than 100 mesh are solid superacid SO4. 2- / ZrO2-Al2O3.

[0009] Furthermore, the regeneration process includes: regenerating the solid superacid SO4 to be regenerated. 2- ZrO2-Al2O3 particles were calcined in a tube furnace and then added to concentrated sulfuric acid. The mixture was then dried and calcined again to obtain regenerated solid superacid SO4. 2- / ZrO2-Al2O3, solid superacid SO4 after regeneration treatment 2- / ZrO2-Al2O3 can make the indicator develop color.

[0010] Furthermore, in step S1, the polymerization reaction temperature is 120~220℃, the polymerization reaction time is 1~6h, and the polymerization reaction pressure is -0.05~-0.095MPa.

[0011] Furthermore, in step S2, the hydrolysis reaction temperature is 30~60℃, the hydrolysis reaction time is 0.5~4h, and the stirring speed is controlled at 70~120r / min.

[0012] Furthermore, solid superacid SO4 2- The preparation methods of / ZrO2-Al2O3 include: Nano-zirconium hydroxide and pseudoboehmite were mixed in a certain proportion, and then a binder was added and mixed evenly to obtain a mixture. The molar ratio of nano-zirconium hydroxide and pseudoboehmite, respectively, was 20~30:1, based on Zr and Al. Deionized water is added to the mixture, and the mixture is stirred to obtain a slurry. After being processed by a granulator and dried, the first granules are obtained. The mass ratio of the mixture to deionized water is 1:1. The first particle was added to concentrated sulfuric acid, and after draining and drying, the second particle was obtained. The second particle was placed in a muffle furnace and calcined to obtain solid superacid SO4. 2- / ZrO2-Al2O3.

[0013] Furthermore, the binder includes carboxymethyl cellulose and polyethylene glycol 600, and the amount of carboxymethyl cellulose and polyethylene glycol 600 added is 0.8~1.2wt%.

[0014] Furthermore, the solid-liquid mass ratio of the first particle to concentrated sulfuric acid is 1:3~5.

[0015] Furthermore, the filtration methods in step S3 include pipeline filtration, bag filtration, centrifugal filtration, and plate pressure filtration, using filter cloth, filter screen, or filter bag with a pore size of 280~320 mesh, preferably 300 mesh.

[0016] (III) Beneficial Effects The above-mentioned technical solution of the present invention has the following beneficial technical effects: The present invention provides a production process for preparing polyaspartic acid based on solid superacid, wherein aspartic acid is used as raw material and solid superacid SO4 with a particle size of 80 mesh or larger is used. 2- The polymerization process, using ZrO2-Al2O3 as a catalyst, yields polysuccinimide. This step utilizes SO4, a solid superacid with an appropriate particle size. 2- ZrO2-Al2O3 is used as a catalyst in the polymerization process, and solid superacid SO4 is used. 2- The proton density of ZrO2-Al2O3 is much greater than that of ordinary inorganic acids. Compared with traditional catalysts such as sulfuric acid and phosphoric acid, its catalytic efficiency is higher, thus reducing the amount of catalyst used and avoiding the discharge of large amounts of acidic wastewater and water consumption. Solid superacid SO4 2- / ZrO2-Al2O3 is obtained according to the solid superacid preparation method of the present invention. Then, the polymerization product is pulverized and sieved to separate particles with a particle size less than 100 mesh. This step is performed using a 100-mesh sieve. The component with a particle size less than 100 mesh is the polymerization product polysuccinimide, and the component with a particle size greater than 100 mesh is the solid superacid catalyst, SO4. 2-ZrO2-Al2O3, used as a catalyst in the polymerization process, has good mechanical strength and can be separated from the polymerization product through simple sieving after pulverization. Finally, the polysuccinimide is pulverized and hydrolyzed, then filtered or electrodialyzed. After the solution pH drops to 3.8-4.0, it is sterilized and dried to obtain polyaspartic acid. The solid superacid catalyst with a particle size greater than 100 mesh is subjected to acid strength titration. Based on the titration results, it can be determined whether it can be used directly. The solid superacid catalyst can be reused at least 7 times, and the exhausted catalyst can be regenerated. That is, it can also be reprocessed to produce solid superacid for recycling using the solid superacid synthesis process. This invention eliminates the step of rinsing the polysuccinimide polymerization product with large amounts of water to remove the acidic catalyst, saving water resources, simplifying the process route, and avoiding the discharge of phosphoric acid-containing wastewater. The method described in this invention can be used for large-scale industrial production, meeting the application needs of polyaspartic acid and its salt products in cosmetics, agriculture, boiler water treatment, and other fields. Attached Figure Description

[0017] Figure 1 This is a flowchart of the production process for preparing polyaspartic acid based on solid superacids according to the present invention. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of the present invention more clearly understood, the present invention will be further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are merely exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, descriptions of well-known structures and technologies are omitted to avoid unnecessary confusion of the concepts of the present invention.

[0019] In this invention, the term "polyaspartic acid" is synonymous with "polyaspartic acid" and "polyaspartic acid". The term "polysuccinimide" is synonymous with "polysuccinimide".

[0020] like Figure 1 As shown, this invention provides a production process for preparing polyaspartic acid based on a solid superacid, wherein the solid superacid is SO4. 2- / ZrO2-Al2O3, including the following steps: S1, made from aspartic acid, using solid superacid SO4 with a particle size of 80 mesh or larger. 2- Using ZrO2-Al2O3 as a catalyst, the reaction under vacuum and high temperature conditions yields a polymerization product, which includes polysuccinimide. The solid superacid catalyst is sulfated zirconium oxide-alumina, i.e., SO42-. 2- / ZrO2-Al2O3. Wherein aspartic acid reacts with the solid superacid SO4. 2-The mass ratio of ZrO2 to Al2O3 is 1:0.01~0.1. In step S1, the polymerization temperature is 120~220℃, preferably 170~200℃, the polymerization time is 1~6h, preferably 2~4h, and the polymerization pressure is -0.05~-0.095MPa. The polysuccinimide is also doped with solid superacid SO4. 2- / ZrO2-Al2O3 catalyst.

[0021] S2, the polymerization product is pulverized and sieved to obtain polysuccinimide with a particle size smaller than 100 mesh, which is then hydrolyzed in an aqueous solution of sodium hydroxide or potassium hydroxide to obtain an aqueous solution of sodium polyaspartate or potassium polyaspartate. The molar ratio of sodium hydroxide or potassium hydroxide to the repeating unit of polysuccinimide is 1.2~0.9:1. This step involves sieving using a 100-mesh sieve; the component with a particle size smaller than 100 mesh is the polymerized product polysuccinimide, and the component with a particle size larger than 100 mesh is the solid superacid catalyst. The hydrolysis reaction temperature is controlled at 30~60℃; the hydrolysis reaction time is 0.5~4h, preferably 1~2h; and the stirring speed during the hydrolysis reaction is 70~120rpm.

[0022] In step S3, the aqueous solution of sodium polyaspartate or potassium polyaspartate is filtered or electrodialyzed until the pH of the solution drops to 3.8-4.0, then sterilized and dried to obtain polyaspartic acid. In step S2, the hydrolysis reaction temperature is 30-60℃, the hydrolysis reaction time is 0.5-4 hours, and the stirring speed is controlled at 70-120 r / min. Filtration methods include pipeline filtration, bag filtration, centrifugal filtration, and plate pressure filtration, with a filter cloth, filter screen, or filter bag having a pore size of 300 mesh.

[0023] Furthermore, the production process also includes: S4, acid titration of particles larger than 100 mesh separated in step S2, including: If the solid superacid SO4 is sieved out 2- Since ZrO2-Al2O3 particles can make the indicator develop color, they are used as the solid superacid SO4 in step S1. 2- The ZrO2-Al2O3 catalyst can be used directly. The acid strength determination of the catalyst in this invention can be performed according to the titration method in Chapter 8 of "Analysis, Testing and Characterization of Industrial Catalysts" edited by Liu Xiyao et al., using m-nitrotoluene (pKa = -11.99) as the Hammett indicator. The acidity requirement for the solid superacid catalyst in this invention is that it should produce an acidic color (yellow) on the indicator during titration, i.e., Hammett acidity function Ho < -11.99. If the sieved solid superacid SO4... 2-If the ZrO2-Al2O3 particles can make the indicator m-nitrotoluene show an acidic color (yellow), then it can directly proceed to step S1 for catalytic polymerization.

[0024] If the solid superacid SO4 is sieved out 2- If the ZrO2-Al2O3 particles fail to produce a color change in the indicator, they must be regenerated. That is, if the sieved solid superacid SO4... 2- If the ZrO2-Al2O3 particles cannot produce an acidic (yellow) color in the indicator m-nitrotoluene, then they undergo regeneration. The regeneration process includes: regenerating the solid superacid SO4 to be regenerated. 2- ZrO2-Al2O3 particles were calcined in a tube furnace and then added to concentrated sulfuric acid. The mixture was then dried and calcined again to obtain regenerated solid superacid SO4. 2- / ZrO2-Al2O3, the regenerated solid superacid SO4 2- / ZrO2-Al2O3 can make the indicator develop color.

[0025] Furthermore, the solid superacid SO4 2- The preparation methods of / ZrO2-Al2O3 include: (1) Nano-zirconium hydroxide and pseudoboehmite are mixed in a certain proportion, and then a binder is added and mixed evenly to obtain a mixture. The nano-zirconium hydroxide and pseudoboehmite are calculated as Zr and Al, respectively, with a molar ratio of 20~30:1. The binder includes carboxymethyl cellulose and polyethylene glycol 600. The amount of carboxymethyl cellulose and polyethylene glycol 600 added is 0.8~1.2wt%, and the preferred amount of carboxymethyl cellulose and polyethylene glycol 600 added is 1wt%.

[0026] (2) Add deionized water to the mixture and stir to obtain a mixed slurry. The slurry is then processed by a granulator to obtain particles with a particle size of about 40 mesh. The particles are then dried at 120°C to constant weight to obtain the first particles. The mass ratio of the mixture to the deionized water is 1:1. (3) After immersing the first particle in concentrated sulfuric acid for 2 hours, the excess liquid is drained off, and the particle is dried at 120°C to obtain the second particle (acidic particle). The solid-liquid mass ratio of the first particle to concentrated sulfuric acid is 1:3~5; (4) The second particle was placed in a muffle furnace and calcined. The calcination conditions were controlled as follows: calcination at 650℃ for 3 h in a static air atmosphere, with a heating rate of 5℃ / min, to obtain solid superacid SO4. 2- / ZrO2-Al2O3. Finally, after sieving, particles with a diameter >80 mesh are obtained and proceed to step S1 for catalysis.

[0027] The following is a detailed description with reference to specific embodiments: Calculation Method: The method for detecting the purity (i.e., polymerization rate) of polysuccinimide in this invention is as follows: Accurately weigh 1.00 g of polysuccinimide product and place it in 20.0 mL of N,N-dimethylformamide. Stir at 60°C until dissolved. Filter the dissolved solution using a sintered glass funnel, and dry the sintered glass funnel along with the filtered insoluble matter at 120°C for at least 4 hours until its mass no longer changes. The formula for calculating the purity of polysuccinimide is: (1) In formula (1), m1 is the total weight of the sand core funnel and insoluble matter after filtration and drying, m0 is the weight of the sand core funnel before filtration, and M is the total weight of the polysuccinimide product sample.

[0028] Furthermore, this invention employs liquid chromatography to detect the molecular weight of polyaspartic acid or its salts using a liquid chromatograph (Shimadzu LC-20A), expressed as number-average molecular weight (M). n ).

[0029] The method for determining the molecular weight of polysuccinimide in this invention is as follows: Polysuccinimide, sodium hydroxide, and water are mixed in a mass ratio of 1:0.045:3. After reacting for 2 hours at room temperature with stirring, the solution is analyzed according to the above-described method for determining the molecular weight of polyaspartic acid or its salts. The obtained molecular weight of polyaspartic acid is then calculated using the formula... Convert to the molecular weight of polysuccinimide, expressed as number-average molecular weight (Mn).

[0030] In this invention, the yield of aspartic acid solid-phase polymerization is calculated as follows: Y = W1 / W2.

[0031] Where W1 is the mass of the polysuccinimide solid particles obtained after polymerization, crushing, and sieving, and W2 is the mass of the raw material aspartic acid. Since the polymerization of aspartic acid to obtain polysuccinimide is a condensation reaction, on average, each molecule of aspartic acid loses two molecules of water in this reaction, so theoretically the maximum yield of complete reaction is 72.93%.

[0032] Example 1.1 Preparation of solid superacid catalysts Solid superacid SO4 2- The preparation methods of / ZrO2-Al2O3 include: (1) Accurately weigh 250.00 g of nano-zirconium hydroxide, 5.10 g of powdered boehmite, 2.55 g of carboxymethyl cellulose, and 2.55 g of polyethylene glycol 600 to obtain a mixture. The molecular formula of boehmite is Al2O3·nH2O, where n is 0.08 to 0.62. The molar ratio of nano-zirconium hydroxide and boehmite, respectively, is 20 to 22:1, calculated as Zr and Al.

[0033] (2) The mixture was placed in a beaker and 260.2 g of deionized water was added. The mixture was mechanically stirred at room temperature to obtain a slurry. The slurry was granulated using a small granulator and the particle size was controlled to be about 40 mesh. Then it was dried at 120°C in a forced-air drying oven to constant weight to obtain the first particles.

[0034] (3) The first particle was immersed in 1000 g of concentrated sulfuric acid and left to stand for 2 h. The excess concentrated sulfuric acid was drained under normal pressure using a sand core funnel. The sand core funnel and the material were placed in a forced-air drying oven and dried at 120°C for 12 h to obtain the second particle. The solid-liquid mass ratio of the first particle to the concentrated sulfuric acid was 1:3.8 (i.e. 260.2:1000).

[0035] (4) The dried second particle is then transferred to a ceramic cup and calcined in a muffle furnace at 650°C for 3 h (heating rate of 5°C / min) under static air atmosphere to obtain solid superacid SO4. 2- ZrO2-Al2O3, solid superacid SO4 with a particle size greater than 80 mesh was sieved. 2- / ZrO2-Al2O3 was used as a catalyst to prepare polyaspartic acid. In the acid strength determination, titration could change the colorless indicator m-nitrotoluene from colorless to yellow, i.e., Hammett acidity function Ho < -11.99.

[0036] 1.2 Preparation of polysuccinimide Using aspartic acid as raw material, and solid superacid SO4 with a particle size of 80 mesh or larger as sieved in step 1.1 preparation method. 2- Polysuccinimide was prepared using ZrO2-Al2O3 as a catalyst. The optimal process conditions were obtained through a three-factor, three-level orthogonal analysis, with polymerization temperature, polymerization time, and the amount of solid superacid catalyst as variables. Specifically, 300.0 g of aspartic acid was reacted with 3.0, 15.0, and 30.0 g of SO42-, respectively. 2- The ZrO2-Al2O3 catalyst (with aspartic acid and solid superacid in mass ratios of 1:0.01 (C1), 0.05 (C2), and 0.1 (C3)) was placed in a 2 L vacuum reactor. After being mechanically stirred and evacuated to below -0.08 MPa, the reactor was heated to 120℃ (A1), 180℃ (A2), and 220℃ (A3) and maintained for 1 h (B1), 3 h (B2), and 6 h (B3), respectively, yielding a pale yellow to yellow solid polymerization product (polysuccinimide-doped solid superacid catalyst particles). The orthogonal settings of the process conditions are shown in Table 1, as are the orthogonal analyses using reaction rate and molecular weight as results.

[0037] Table 1. Orthogonal experimental design and results

[0038] Table 2 Analysis of Reaction Rate Results

[0039] Table 3 Analysis of molecular weight results

[0040] Table 2 shows that, in the orthogonal analysis with reaction rate as the result, the optimal combination of process conditions A3B3C3, determined by calculating the means, is: temperature 220℃, time 6 h, and catalyst dosage 30.0 g; and through F... 0.05 As can be seen, all three factors are significant. The orthogonal analysis in Table 3, with molecular weight as the result, is consistent with the conclusions in Table 2.

[0041] 1.3 Preparation of polysuccinimide under optimal process conditions (A3B3C3 combination) 300.0 g of aspartic acid and 30.0 g of SO4 2- ZrO2-Al2O3 catalyst (particle size greater than 80 mesh) was placed in a 2 L vacuum reactor (aspartic acid to catalyst mass ratio of 1:0.1). After being vacuumed to below -0.08 MPa with mechanical stirring, the temperature was raised to 220℃ and maintained for 6 h, yielding a yellow solid. The yellow solid was pulverized in batches using a small traditional Chinese medicine pulverizer, and 215.50 g of solid particles with a particle size <100 mesh (polysuccinimide, yield 71.83%) and 31.02 g of solid particles with a particle size >100 mesh were screened using a 100-mesh sieve. The polymerization results are shown in Example 10 of Table 4. Simultaneously, multiple parallel experiments for the preparation of polysuccinimide were continuously conducted under the experimental conditions in 1.3 (all catalysts were freshly prepared to ensure the parallelism of the experiments). The results are shown in Examples 11-16 of Table 4. As shown in Table 4, the RSD of both the reaction rate and the yield was less than 1%, and the molecular weight M... n The RSD is less than 10%, indicating that the reaction process has good stability after repeated runs.

[0042] Table 4 Preparation of polysuccinimide

[0043] 1.4 Solid superacid SO4 2- Reuse of ZrO2-Al2O3 catalyst Following the experimental conditions described in step 1.3 above, multiple experiments were conducted consecutively to prepare polysuccinimide, and the effects on SO4 were investigated. 2-The reusability of the ZrO2-Al2O3 catalyst was verified, with each addition being a recycled product of the catalyst used in the previous experiment. The results are shown in Table 5. It can be seen that when the experiment was conducted for the 7th time, the Ho value of the catalyst was > -11.99, meaning the acidity decreased to a level that could not meet the requirements of a solid superacid. Meanwhile, the reaction rate, molecular weight, and yield remained relatively stable across these 7 experiments.

[0044] Table 5 Solid superacid SO4 2- Verification of the Reusability of ZrO2-Al2O3 Catalyst

[0045] 1.5 Pilot-scale scale-up of solid-state polymerization process Referring to the experimental conditions in step 1.3 above, 50.0 kg of aspartic acid and 5.0 kg of SO4 were added. 2- The ZrO2-Al2O3 catalyst (particle size greater than 80 mesh) was placed in a 300 L vacuum reactor. Under mechanical stirring, the pressure was evacuated to below -0.08 MPa, then heated to 220℃ and maintained for 6 h to obtain a yellow solid. The yellow solid was pulverized in batches using a dust-free pulverizer, and 35.19 kg of solid particles with a diameter <100 mesh (yield 70.38%) and 5.12 kg of solid particles with a diameter >100 mesh were screened using a 100-mesh sieve. Furthermore, multiple consecutive experiments were conducted according to step 1.4 above, and the results are shown in Table 6. It is evident that the process described in this invention exhibits excellent reproducibility after pilot-scale production, proving its suitability for industrial-scale production.

[0046] Table 6. Pilot-scale preparation results of polysuccinimide

[0047] 1.6 Solid superacid SO4 2- Regeneration preparation of ZrO2-Al2O3 catalyst Accurately weigh 300.0 g of the solid superacid catalyst obtained after Example 23 above, transfer it to a graphite boat and place it in the quartz tube of a tube furnace. Heat the catalyst to 450°C at a rate of 10°C / min under an air flow of 3 L / min and maintain the temperature for 1 h. After natural cooling to room temperature, 268.3 g of solid is obtained. This solid is then immersed in concentrated sulfuric acid at a solid-liquid ratio of 1:4 for 2 h. Excess liquid is drained off, and the catalyst is dried at 120°C. The dried acid particles are placed in a muffle furnace and calcined at 650°C for 3 h under static air atmosphere at a heating rate of 5°C / min to obtain regenerated solid superacid SO4. 2- / ZrO2-Al2O3, then sieved to obtain particles with a diameter >80 mesh.

[0048] The regenerated solid superacid catalyst was used to prepare polysuccinimide under the process conditions described in step 1.3 above, and the polymerization results are shown in Table 7. It can be seen that the method described in this invention can regenerate the solid superacid catalyst, and the regenerated catalyst does not affect the polymerization reaction results.

[0049] Table 7. Catalytic results of the regenerated solid superacid.

[0050] 1.7 Preparation of polyaspartic acid 1.7.1: Hydrolysis to prepare sodium polyaspartate Accurately weigh 2.47 g of NaOH and add it to 30.0 mL of deionized water, stirring until completely dissolved. Accurately weigh 6.00 g of the polysuccinimide solid prepared in Example 10 and add it to the above NaOH aqueous solution. Stir at 40°C for 2 h at a stirring rate of 100 rpm to obtain a yellowish-brown transparent liquid. The molar ratio of sodium hydroxide to polysuccinimide repeating units is 1:1. After filtering with a 300-mesh filter cloth to remove a small amount of residual insoluble matter, a sodium polyaspartate aqueous solution is obtained, with a pH of 9.87 (the hydrolysis of polysuccinimide consumes NaOH, so measuring the pH value can characterize the hydrolysis reaction rate of polysuccinimide). Using the above method, 10 parallel experiments were conducted using the polysuccinimide solid prepared in Example 10 as a sample. The results are shown in Table 8, indicating that the hydrolysis reaction of polysuccinimide has good stability under the above process conditions.

[0051] Table 8 Preparation of sodium polyaspartate aqueous solution

[0052] 1.7.2 Preparation of Polyaspartic Acid Accurately weigh 20.0 kg of the sodium polyaspartate aqueous solution prepared under the experimental conditions in step 1.7.1, and dilute it with 80.0 kg of deionized water. Adjust the pH of the diluted solution to 3.81 with phosphoric acid. Perform ultrafiltration using a MWCO 3 kDa membrane. After the volume and pH of the retentate stabilize, collect the retentate, which is the polyaspartic acid aqueous solution, a yellow transparent liquid with a pH of 3.96. Sterilize and dry it to obtain a pale yellow polyaspartic acid powder.

[0053] 1.7.3 Hydrolysis preparation of potassium polyaspartate and polyaspartic acid Accurately weigh 3.46 kg of KOH and add it to 30.0 L of deionized water, stirring until completely dissolved. Accurately weigh 6.00 kg of the polysuccinimide solid prepared in Example 18 of step 1.5 above, add it to the above KOH aqueous solution, and stir in a 40°C water bath for 2 h at a stirring rate of 100 rpm to obtain a yellowish-brown transparent liquid. The molar ratio of potassium hydroxide to polysuccinimide repeating units is 1:1. After filtering out a small amount of residual insoluble matter using a 300-mesh pipeline filter, a potassium aspartate aqueous solution is obtained, with a pH of 9.76. The obtained potassium aspartate aqueous solution is then filtered or electrodialyzed until the pH of the solution drops to 3.8-4.0, and then sterilized and dried to obtain a light yellow polyaspartic acid powder.

[0054] This invention discloses a production process for preparing polyaspartic acid based on solid superacid. In the synthesis of polyaspartic acid and its salts, a solid superacid with a suitable particle size is used as a catalyst in the polymerization process. Its main advantages include: 1. Solid superacid SO4 2- The proton density of ZrO2-Al2O3 is much greater than that of ordinary inorganic acids, resulting in higher catalytic efficiency as a polymerization catalyst and reducing the amount of catalyst used in the polymerization process.

[0055] 2.SO4 2- ZrO2-Al2O3, as a catalyst in the polymerization process, has good mechanical strength. After the polymerization product is crushed, it can be separated from the product by simple sieving. It can also be reused directly after passing the acid strength titration. Even if the acid strength titration fails, it can be reprocessed into a solid superacid for recycling using the solid superacid synthesis process.

[0056] 3. It eliminates the need for the polymerization product polysuccinimide to be rinsed with a large amount of water to remove the acidic catalyst, thus saving water resources, simplifying the process route, and avoiding the discharge of phosphoric acid-containing wastewater.

[0057] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.

Claims

1. A production process for preparing polyaspartic acid based on solid superacid, characterized in that: The solid superacid is SO4 2- / ZrO2-Al2O3, comprising the following steps: S1, using aspartic acid as raw material, solid superacid SO4 with a particle size of more than 80 mesh 2- / ZrO2-Al2O3 is used as a catalyst, and a polymerization product is obtained by reaction under vacuum and high temperature conditions, wherein the polymerization product includes polysuccinimide; S2, crushing the polymer product and sieving particles with a particle size of less than 100 mesh to obtain polysuccinimide and placing it in an aqueous solution of sodium hydroxide or potassium hydroxide for hydrolysis to obtain a sodium polyaspartate or potassium polyaspartate aqueous solution; S3, filtering or electrodialyzing the aqueous solution of sodium polyaspartate or potassium polyaspartate, sterilizing and drying to obtain polyaspartic acid.

2. The production process for preparing polyaspartic acid based on solid superacid according to claim 1, characterized in that: In the step S1, the aspartic acid and the solid superacid SO4 2- The mass ratio of / ZrO2-Al2O3 is 1:0.01~0.

1.

3. The production process for preparing polyaspartic acid based on solid superacid according to claim 1, characterized in that: In the step S2, the molar ratio of the sodium hydroxide or the potassium hydroxide to the polysuccinimide repeating unit is 1.2-0.9:

1.

4. The production process for preparing polyaspartic acid based on solid superacid according to claim 1, characterized in that: The production process also includes: S4, performing acid titration on the particles with a particle size greater than 100 mesh screened out in step S2, comprising: If the solid superacid SO4 is screened out 2- / ZrO2-Al2O3 particles can make the indicator color, so it is used as the solid superacid SO4 in step S1 2- / ZrO2-Al2O3 catalyst is used directly; If the solid superacid SO4 is screened out 2- / ZrO2-Al2O3 particles cannot make the indicator color, so they are regenerated; wherein the particles with a particle size greater than 100 mesh are solid superacid SO4 2- / ZrO2-Al2O3.

5. The production process for preparing polyaspartic acid based on solid superacid according to claim 4, characterized in that: The regeneration process comprises: treating the solid superacid SO4 to be regenerated 2- / ZrO2-Al2O3 particles are calcined in a tube furnace and then added to concentrated sulfuric acid, followed by drying and calcination to obtain regenerated solid superacid SO4 2- / ZrO2-Al2O3, the solid superacid SO4 after the regeneration treatment 2- / ZrO2-Al2O3 can make the indicator show color.

6. The production process for preparing polyaspartic acid based on solid superacid according to claim 1, characterized in that: In the step S1, the polymerization reaction temperature is 120-220° C., the polymerization reaction time is 1-6 hours, and the polymerization reaction pressure is -0.05-0.095 MPa.

7. The production process for preparing polyaspartic acid based on solid superacid according to claim 1, characterized in that: In the step S2, the hydrolysis reaction temperature is 30-60° C., and the hydrolysis reaction time is 0.5-4 h.

8. The production process for preparing polyaspartic acid based on solid superacid according to claim 1, characterized in that: The solid superacid SO4 2- The preparation method of ZrO2-Al2O3 comprises: The nano zirconium hydroxide and pseudo-boehmite are mixed in proportion, and then a binder is added and mixed evenly to obtain a mixed material, wherein the nano zirconium hydroxide and pseudo-boehmite are respectively calculated as Zr and Al, and the molar ratio is 20-30:1; Adding deionized water to the mixture, stirring to obtain a mixed slurry, treating the mixed slurry with a granulator, and drying the mixed slurry to obtain first particles, wherein the mass ratio of the mixture to the deionized water is 1:1; Adding the first particles into concentrated sulfuric acid, draining and drying to obtain second particles; The second particles are placed in a muffle furnace and calcined to obtain solid superacid SO4 2- / ZrO2-Al2O3.

9. The production process for preparing polyaspartic acid based on solid superacid according to claim 8, characterized in that: The binder includes carboxymethyl cellulose and polyethylene glycol 600, and the added amounts of the carboxymethyl cellulose and the polyethylene glycol 600 are both 0.8-1.2 wt %.

10. The production process for preparing polyaspartic acid based on solid superacid according to claim 8, characterized in that: The solid-liquid mass ratio of the first particles to concentrated sulfuric acid is 1:3-5.

Citation Information

Patent Citations

  • Solid super acidic catalyst and preparation method thereof

    CN101890355A

  • Method for preparing 40% sodium polyaspartate aqueous solution

    CN103554495A

  • Preparation method of cosmetic grade sodium polyaspartate

    CN109679092A

  • Touch sensor device including pressure sensor and manufacturing method thereof

    KR102288183B1